1998
DOI: 10.1007/bf02389331
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the middle cerebral artery after excision of a giant fusiform aneurysm

Abstract: A patients with a giant fusiform aneurysm of the left inferior trunkus of the middle cerebral artery (MCA) is presented. The size of the aneurysm was 5 cm at its largest diameter. Retrograde flow was well developed. After the application of temporary clips the aneurysm was excised and microsurgical reconstructions were undertaken. Adequate flow in the reconstructed MCA trunkus was maintained. This rare case is discussed in the light of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…This contrasts with that of patients with saccular aneurysms 36) . Our study confirms previous reports that spontaneous fusiform aneurysms are more often found in younger patients 2,4,6,9,13,19,26,29,31,34,35) and are more frequent in men 6,13,28,35) .…”
supporting
confidence: 92%
See 4 more Smart Citations
“…This contrasts with that of patients with saccular aneurysms 36) . Our study confirms previous reports that spontaneous fusiform aneurysms are more often found in younger patients 2,4,6,9,13,19,26,29,31,34,35) and are more frequent in men 6,13,28,35) .…”
supporting
confidence: 92%
“…It is defined as a circumferential arterial dilatation resulting from pathological involvement of the entire artery 2,4,9,28,34) . All aneurysms exhibit a spindle shape when viewed externally 6) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations